Association between organophosphorus pesticides and obesity among American adults - Wei Xu; Yinqiao Dong; Shiping Liu; Fan Hu; Yong Cai (BMC, 2024)
Abstract Objective To investigate any connections between urinary organophosphorus pesticide (OPP) metabolites and adiposity measures. Methods In this study, data from the National Health and Nutrition Examination Survey (NHANES) projects from 2003 to 2008, 2011 to 2012, and 2015 to 2018 were analysed. Obesity was defined as a body mass index (BMI) of 30 kg/m² or higher. Abdominal obesity was defined as a waist circumference (WC) over 102 cm for men and 88 cm for women. Four urinary OPP metabolites (dimethyl phosphate [DMP], diethyl phosphate [DEP], dimethyl phosphorothioate [DMTP], and diethyl phosphorothioate [DETP]) and adiposity measures were examined using multiple linear regression and logistic regression analyses. The correlations between a variety of urinary OPP metabolites and the prevalence of obesity were investigated using weighted quantile sum regression and quantile g-computation regression. Results In this analysis, a total of 9,505 adults were taken into account. There were 49.81% of male participants, and the average age was 46.00 years old. The median BMI and WC of the subjects were 27.70 kg/m2 and 97.10 cm, respectively. Moreover, 35.60% of the participants were obese, and 54.42% had abdominal obesity. DMP, DMTP, and DETP were discovered to have a negative correlation with WC and BMI in the adjusted models. DMP (OR = 0.93 [95% CI: 0.89-0.98]), DEP (OR = 0.94 [95% CI: 0.90-0.99]), DMTP (OR = 0.91 [95% CI: 0.86-0.95]), and DETP (OR = 0.85 [95% CI: 0.80-0.90]) exhibited negative associations with obesity prevalence. Similar correlations between the prevalence of abdominal obesity and the urine OPP metabolites were discovered. Moreover, the mixture of urinary OPP metabolites showed negative associations with adiposity measures, with DMTP and DETP showing the most significant effects. Conclusion Together, higher levels of urinary OPP metabolites in the urine were linked to a decline in the prevalence of obesity.